Campaña de comunicación en redes sociales para difundir la cultura del cantón Santa Rosa. - Ochoa Garrido, Johanna Lisseth; Sanmartin Tomala, Jessika Dennisse (Machala, 2021)
Within the Santa Rosa canton, information related to cultural issues is scarce, in the absence of initiatives that promote the dissemination of their culture, people are at risk of forgetting the legacy left by our ancestors and those knowledge that have been passed from one generation to another, over the years. Santa Rosa is a city full of history, customs, traditions and beliefs, which the new generations need and deserve to know with the sole purpose of enthhether the cultural heritage (its origin and its essence) remains alive through time in the memory and hearts of each one of them. Therefore, the purpose of this research work, with a process of systematization of practical experiences of Research or Intervention, was the development of a communication campaign in social networks for the dissemination of the culture of Santarroseña. Initially, a survey was applied to the citizens of Santarroseños where it could be evidenced that 62.6% of the respondents knew little about the culture of their canton, in addition accurate data was obtained for the realization of the campaign such as: the elements that are part of their culture, the target audience that in this case were the children, What social networks to use? and the cultural values that should be disseminated. From this was born the interest of executing actions such as the creation of communication pieces that motivate children to know about the history, cultural identity, monuments, sculptures, beliefs, customs and traditions of their canton. The objectives were aimed at executing a campaign to disseminate the cultural identity of the Santa Rosa Canton, in order to preserve its culture. A mixed approach was used, since techniques such as the online survey towards the citizens of Santarroseños and the focus group to children between the ages of 5 and 11 years old were used, the application of these two techniques allowed to know the impact of the campaign. The communication products that were developed were: animated videos of the best known legends of the canton, an online puzzle, flyers and infographics, to capture the attention of the audience; these products were published on the Facebook and Instagram account of "Orotopia", a Linking Project of the UTMACH, this page is aimed at making visible the Cultural Heritage of the province of El Oro, so it was considered appropriate to use this medium to carry out the campaign. The results obtained allowed us to know that the realization of a campaign that disseminates cultural contents of the canton is feasible so it could be evidenced in the acceptance that "The magic of Santa Rosa" had in the audience after sharing, commenting, reacting to each of the publications uploaded to the aforementioned page. The evaluation of the intervention was carried out with a focus group of children through a meeting via Zoom where they were explained in a didactic way about their culture, contributing to a broad and meaningful learning, achieving favorable results from them.
Dentro del cantón Santa Rosa, la información relacionada con temas culturales es escasa, ante la falta de iniciativas que fomenten la difusión de su cultura las personas están en riesgo de olvidar el legado dejado por nuestros ancestros y aquellos conocimientos que han pasado de unas generaciones a otras, a lo largo de los años. Santa Rosa, es una ciudad llena de historia, de costumbres, de tradiciones y de creencias, que las nuevas generaciones necesitan y merecen conocer con el único fin de que la herencia cultural (su origen y su esencia) permanezca viva a través del tiempo en la memoria y corazones de cada uno de ellos. Por ello el propósito del presente trabajo investigativo, con proceso de sistematización de experiencias prácticas de Investigación o Intervención, fue el desarrollo de una campaña de comunicación en redes sociales para la difusión de la cultura santarroseña. Inicialmente, se aplicó una encuesta a los ciudadanos santarroseños donde se pudo evidenciar que el 62, 6% de los encuestados conocía poco sobre la cultura de su cantón, además se obtuvo datos precisos para la realización de la campaña como: los elementos que hacen parte de su cultura, el público objetivo que en este caso fueron los niños, ¿Qué redes sociales utilizar? y los valores culturales que debían ser difundidos. A partir de ello nació el interés de ejecutar acciones como la creación de piezas comunicacionales que motiven a los niños a conocer sobre la historia, la identidad cultural, los monumentos, esculturas, creencias, las costumbres y tradiciones de su cantón. Los objetivos planteados estuvieron direccionados en ejecutar una campaña para difundir la identidad cultural del Cantón Santa Rosa, con la finalidad de preservar su cultura. Se empleó un enfoque mixto, ya que se usaron técnicas como la encuesta online hacia los ciudadanos santarroseños y el grupo focal a niños entre las edades de 5 a 11 años, la aplicación de estas dos técnicas permitieron conocer el impacto de la campaña. Los productos comunicacionales que se elaboraron fueron: videos animados de las leyendas más conocidas del cantón, un rompecabezas online, flyers e infografías, para lograr captar la atención de la audiencia; estos productos fueron publicados en la cuenta de Facebook e Instagram de “Orotopía”, un Proyecto de vinculación de la UTMACH, esta página está dirigida en visibilizar el Patrimonio Cultural de la provincia de El Oro, por ello se consideró oportuno usar este medio para llevara a cabo la campaña. Los resultados que se obtuvieron permitieron conocer que la realización de una campaña que divulgue contenidos culturales del cantón es factible así se pudo evidenciar en la aceptación que tuvo “Lo mágico de Santa Rosa” en la audiencia tras compartir, comentar, reaccionar a cada una de las publicaciones subidas a la página antes mencionada. La evaluación de la intervención se realizó con un grupo focal de niños mediante una reunión vía Zoom donde se les explicó de manera didáctica sobre su cultura, contribuyendo a un aprendizaje amplio y significativo, logrando obtener resultados favorables por parte de ellos.
Keywords: IDENTIDAD; PATRIMONIO; TRADICION; COSTUMBRE